Mine Closure, Sustainable Development & Corporate Social Responsibility: An Emerging Paradigm in Mine Planning - Bandopadhyay, S. (Екологія і природокористування, 2013)
Mining faces distinctive challenges in the future. The concept of closure and decommissioning now involves the entire mining industry. As a consequence, it is essential to recognize in the mine planning process that a commitment to mitigating the environmental effects of a project is a fundamental component, and a closure plan is an important aspect of the mining project. Mining companies must be committed to seeking out the cleanest, most environmentally sound mining techniques.